Synthesis and Physico-Chemical Characteristics of Some Dioxouranium(VI) Complexes of N-isonicotinamido-3-Methoxy-4-hydroxy Benzalaldimine and N-isonicotinamidocinnamalaldimine† - Singh, Laksman; Neelam Tyagi, Miss; Pal Dhaka, Naresh (Asian Journal of Chemistry, 2010)
A series of 12 new complexes of dioxouranium(VI) with hydrazonesof isonicotinic acid hydrazide, viz., N-isonicotinamido- cinnamalaldimine(INH-CIN) and N-isonicotinamido-3-methoxy-4-hydroxy benzalaldimine(INH-VAN) having the general composition UO2X2·nL (X = Br-,I-, CH3COO-, NO3, NCS-, n = 2; X = CIO4-, n = 3; L = INH-VAN or INHCIN) were prepared in non-aqueous media and characterized on the basis of elemental analyses, electrical conductivity, magnetic moment and IR spectral studies. In all the complexes these ligands act as neutral bidentate (N, O) ligands. In all dioxouranium(VI) complexes, the v1 and v3 modes are assigned in the 845-825 cm-1 and 930–910 cm-1 respectively. Wilson's G-F matrix method was used to determine the stretching and interaction force-constants from which the U—O bond distances were calculated using Badger's formula. The calculated data shows that U—O bond length decreases with increase in the value of symmetric stretching frequency (VI). A plot of (V1 + V3) vs. force constants gave a straight line. The calculated values of the U—O bond distances in the present complexes are close to 1.73-1.74 Å. The probable coordination number of U(VI) is 8 or 10, depending on the nature of anions. Thermal properties are also discussed.